2019
DOI: 10.3390/ijerph17010013
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Health-Supportive Neighborhoods: A Multilevel Analysis of Built Environment, Perceived Disorder, Social Interaction and Mental Health in Beijing

Abstract: Mental health is an exceedingly prevalent concern for the urban population. Mounting evidence has confirmed the plausibility of high incidences of mental disorders in socioeconomically disadvantaged neighborhoods. However, the association between the neighborhood built environment and individual mental health is understudied and far from conclusive, especially in developing countries such as China. The underlying mechanism requires in-depth analysis combining potential intermediates such as perceived environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 66 publications
2
22
1
Order By: Relevance
“…Second, our results imply that, different from physical health, individuals' mental health is more implicitly affected by their surrounding environment. The internal mechanism of this influence is complicated, and more research is needed to test and clarify possible mediators ( 63 ). Third, the present study bridges a knowledge gap in research on the association between the relative extent of green space, residents' mental health, and potential mediating mechanisms between them in a Chinese city other than Beijing ( 36 ) or Guangzhou ( 4 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Second, our results imply that, different from physical health, individuals' mental health is more implicitly affected by their surrounding environment. The internal mechanism of this influence is complicated, and more research is needed to test and clarify possible mediators ( 63 ). Third, the present study bridges a knowledge gap in research on the association between the relative extent of green space, residents' mental health, and potential mediating mechanisms between them in a Chinese city other than Beijing ( 36 ) or Guangzhou ( 4 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The location and surrounding environments, such as the surrounding land use, light, air, and provided facilities also have a relationship with mental health (Boadi et al, 2005;Kim & Yoo, 2019;James et al, 2017). The built environment, especially housing, is associated with mental health more than physical health (Barros et al, 2019;Tao et al, 2020). The low-cost housing location is usually in a lower estate value and generally in a deprived area.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between the built environment and mental health findings is still limited and conclusive. According to Tao, Yang, and Chai (2020) and Barros et al (2019), the built environment of a neighbourhood gives a resident an initial feeling of safety and disorder, which can be an emotional response that can improve or harm residents' social wellbeing and mental health depending on their feelings. There are abundant studies that have found that a built environment can also become a determinant affecting the risk of mental disorders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extensive research indicates that the built environment can have an impact on population health, affecting diabetes and obesity [ 3 ], respiratory diseases [ 4 ] and cardiovascular diseases [ 5 ]. At the same time, built environments can have a preventative role in human health by promoting healthy behaviours, such as physical activity [ 6 ], healthy diet [ 7 ] and opportunities for social cohesion and restoration [ 8 ]. Despite the importance of the built environment for children’s health and development [ 2 ], including potential effects on obesity and metabolic syndrome in adult life [ 9 ], less evidence exists on the influences of the built environment on children’s health behaviours.…”
Section: Introductionmentioning
confidence: 99%